(3GdLdjS GdUGdM GdcGaj hGdCfjS GdfGUM GdTGajs - (3GdeYGaj Hf RcQjG Hf jMji GdLQjQqj GdfgQhGfj, nCoHh GdnanQL GHf WQGQ,J (B390 (3g` s
(3ChdgG (B:s
(3CNHQfG CHh GdYR CMeO Hf YHjO Gddg Hf eMeO Hf cGOT GdSdei ELGRI CeG HYO hSfI NdJ acQJ ai CTjGA ef YLGH s
(3BNQgG (B:s
(3hJaVjd ajeG gfGdc JHjjf ajeG CeddfGg ef GdfXe hGdfKQ ef TQM eNJUQ CHj YeQ GdLQei ai GdfMh hef fXQ ajeG gfGdc JHjf dg eG hUafG Ef TGA Gddg ced HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B260 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B302s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs